IMPROVING STUDENTS’ WRITING SKILLS USING COOPERATIVE LEARNING AT SMPN 2 SUKODONO - Hertiki - Hertiki; Juliati Juliati (Journal of English for Academic and Specific Purposes, 2019)
This research was conducted in order to find out whether using Cooperative Learning is effective to improve students’ writing skills or not. Also, it is to find the result of the students’ ability in writing when the researcher using Cooperative Learning. The main problems were: (1) the students seldom do the writing tasks; (2) they had difficulty in grammar during writing; (3) they got difficulty in developing ideas. The research methodology of this research was Classroom Action Research (CAR), which was done in two cycles. Every cycle consists of four steps, that is planning, implementing, observing, and reflecting. The techniques for collecting the data were documentation, observation and test. The subject of this research is class VII-H that consists of 33 students, one English teacher as a collaborator and the researcher herself involved in this research. Based on the results of the study, it showed that the mean score of students increased from 62.9 to 74.7 in cycle 1. On the other hand, in cycle 2, the mean score increased classically from 76.7 to 83.5. Considering the data above, the achievement of the students in writing skills has achieved the indicator of success using cooperative learning. From the result, the researcher concluded that applying cooperative learning can improve writing skills for seventh grade of SMPN 2 Sukodono.Keywords: classroom action research, writing skills, cooperative learning